Multilevel Modelling with MultEcore: A Contribution to the MULTI Process Challenge - Rodriguez, Alejandro; Macias, Fernando (2019 ACM/IEEE 22nd International Conference on Model Driven Engineering Languages and Systems Companion (MODELS-C), 2019)
The MULTI Challenge is intended to encourage the Multilevel Modelling research community to submit solutions to the same, well described problem. This year the subject domain has been changed with respect to previous editions (MULTI Bicycle challenge in 2017 and 2018). This paper presents one solution in the context of process management, where universal properties of process types along with task, artifact and actor types together with possible particular occurrences for scoped domains are modelled. We discuss our solution highlighting both the strengths and limitations of our approach, using the MultEcore tool.